Differences Between Incarcerated and Nonincarcerated Youth in the English-Speaking Caribbean - Freemon, Kayla R. (International criminal justice review, 2023)
Incarcerated youth across the English-speaking Caribbean engage in high levels of offending before their detention. However, we know little about whether youth detained in juvenile justice systems in the region are those with the highest offending levels. As in nations beyond the region, some groups of youth in the Caribbean may be disproportionately overrepresented in the system despite their offending levels, such as by race or gender. Using samples of secondary school students and incarcerated youth, the present study examines: (1) do incarcerated youth self-report engaging in more delinquency prior to being detained than those not incarcerated and (2) are there demographic or risk/protective factors differences between incarcerated and nonincarcerated youth? We find that, compared to nonincarcerated youth, incarcerated youth self-report higher levels of delinquency, in general, and across violent offending, property offending, and drug involvement. When we used propensity score matching to match youth by their involvement in delinquency, disparities in multiple demographic and risk/protective factors emerge between incarcerated and nonincarcerated youth. Our findings point toward racial disparities in the use of incarceration, with African descent youth more likely to be incarcerated. We contextualize our results for youth justice in the Caribbean.